STRATEGI KOMUNIKASI PEMASARAN PERUMAHAN TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN DI MASA PANDEMI COVID 19 (Studi Kualitatif Di Perumahan Bekasi Timur Regency) - BUDI SUSWANTO (Interpretasi: Communication & Public Relations, 2021)
During the current pandemic, the economic decline is very pronounced. Oneindicator can be seen from the decline in home sales by as much as 60 percent. This is a challenge for housing marketers, to continue to be able to market housing. One of the ways marketers use social media in marketing housing. Bekasi Timur Regensi(BTR) housing marketers market using social media Instagram, Facebook, andWhatsApp. This study used five key informants. Qualitative research approach, withthe research method used case studies. Descriptive is used for this type of research.Research conclusion: first, the use of social media is an effective and efficient way ofmarketing communication. Second, even though it is considered quite effective andefficient, the use of social media is still constrained by technology, it is different when we meet in person. Third, the decision to buy housing remains in the hands of the buyer. Although it is true that in the housing management, there is a selectionregarding the income that potential customers will get.